LINGUOCULTUROLOGICAL CLASSIFICATION OF UZBEK DANCE TERMS (Scientific journal of the Fergana State University, 2023)
In the article the terminology of the national Uzbek dance, the systematization of its structure and linguocultural features of its historical formation are investigated.